Polycystic Ovary Syndrome (PCOS): A Biochemical and Physiological Perspective on a Common Gynaecological Disorder in a Local Hospital of Peshawar: PCOS: Biochemical and Physiological Perspective on a Gynaecological Disorder - Afridi, Sanodia; Noor, Somaya; Shah, Summeira Jabeen; Tariq, Erum; Razaq, Muhammad; Saifullah, Shabina (Pakistan Journal of Health Sciences, 2025)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting reproductive and metabolic health. It is characterized by hormonal imbalances, insulin resistance, dyslipidemia, and chronic inflammation, increasing long-term health risks. Objective: To compare biochemical, metabolic, and ultrasound markers in women with and without PCOS. Methods: A comparative cross-sectional study was conducted at Health Net Hospital, Peshawar, over six months. In total, 110 participants were recruited and divided equally into 2 groups, with each group considered as PCOS (n=55) and Non-PCOS (n=55). PCOS was diagnosed using the Rotterdam Criteria. Hormonal, metabolic, and inflammatory markers, including luteinizing hormone, Follicle-Stimulating Hormone, testosterone, Dehydroepiandrosterone Sulphate, Anti-Müllerian Hormone, fasting glucose, Homeostasis Model Assessment of Insulin Resistance (HOMA-IR), lipid profile, C-reactive protein, Malondialdehyde, and Total Antioxidant Capacity (TAC), were analyzed. Ultrasound findings assessed ovarian morphology, endometrial thickness, and stromal resistance index. Data were analyzed using SPSS. Results: PCOS patients had significantly higher BMI, insulin resistance, and androgen levels. Luteinizing hormone/Follicle-Stimulating Hormone ratio and Anti-Müllerian Hormone were elevated, while Follicle-Stimulating Hormone was lower. Metabolic markers showed increased fasting glucose, HOMA-IR, and dyslipidaemia, with higher LDL and triglycerides and lower HDL. Inflammatory and oxidative stress markers (C-reactive protein, Malondialdehyde) were significantly elevated, while TAC was reduced. Ultrasound findings showed increased endometrial thickness and ovarian stromal resistance in PCOS. Conclusions: It was concluded that PCOS is associated with significant hormonal, metabolic, and inflammatory disturbances. Elevated androgens, insulin resistance, and oxidative stress highlight the need for early screening and a multidisciplinary approach for Effective Management.